The specific conditions of the valorization of Capital in a Dependent Nation : The case of Argentina (2002-2014) - López, Emiliano; Barrera Insua, Facundo (2019)
In this article, we examine the tendency toward stagnation in the Argentinean economy, as a dependent economy, in the context of a new development model that emerged in this country before the neoliberal crisis in 2001. The initial boom of accumulation in the period 2002-2007, after the devaluation of the peso, has been challenged for various tensions that emerged, in our perspective, for the dependent economic structure of Argentina in the years 2007 and 2008. These tensions were increased after the European economic crisis and China's slowdown in 2012-2014, leading to the stop of the accumulation process and the start of economic transition to the different development model.
Keywords: Dependent countries; Marxian categories; Development model; Argentina; Stagnation; Historia económica argentina; Economía argentina; Crisis económicas; Modelos económicos